2012
DOI: 10.4028/www.scientific.net/ssp.184.98
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy Relaxation in Ca<sub>3</sub>Co<sub>4</sub>O<sub>9+δ</sub> Ceramics

Abstract: Ca3Co4O9+δceramic powders were synthesized by the polymerized complex (PC) method. The same Ca3Co4O9+δceramic bar were treated in turn with three different processes of oxygen treatment: with no treatment, with oxydol (H2O2) treatment, and with N2treatment. Dynamic mechanical analysis (DMA) was performed from 123 to 623 K at rate of 1 K/min while the measuring frequencies are 0.05, 0.1, 0.25, 0.5, 1, 2, and 5 Hz. Two internal friction peaks are observed: one at the temperature range from 360 to 400 K (a broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
(21 reference statements)
2
4
0
Order By: Relevance
“…However, at high temperatures, the oxygen vacancies actively take part in the conduction process due to their high mobility. From the calculation, it is found that the range of activation energy lies between 0.99-1.53 eV, which is comparable with the other perovskite-based compounds, as reported by different authors [61,57]. The above observations confirmed the increase in activation energy with the increase of La 3+ concentration in the composition.…”
Section: Impedance Analysissupporting
confidence: 88%
“…However, at high temperatures, the oxygen vacancies actively take part in the conduction process due to their high mobility. From the calculation, it is found that the range of activation energy lies between 0.99-1.53 eV, which is comparable with the other perovskite-based compounds, as reported by different authors [61,57]. The above observations confirmed the increase in activation energy with the increase of La 3+ concentration in the composition.…”
Section: Impedance Analysissupporting
confidence: 88%
“…43 The activation energy (E a ) is dependent on the concentration of OVs: E a = 0 eV for stoichiometric ABO 2.8 , 0.5 eV for ABO 2.9 , 1.0 eV for ABO 2.95 , and 2.0 eV for ABO 3 . 44,45 According to our results, activation energy increases with the increasing concentration of Ba 2+ , this successfully indicates that Ba 2+ doping can reduce the volatilization of Pb 2+ and restrict the generation of OVs. Based on the values of activation energy calculated from impedance, we can reasonably conclude that the relaxation observed in high temperature region was contributed to the short-range hopping of OVs, and the slight higher activation energy was due to low concentration of OVs.…”
Section: Resultssupporting
confidence: 64%
“…As the samples considered here were not processed at high oxygen partial pressure, we conclude that despite having been batched to favor A‐site vacancy compensation, the source of the reduction in conductivity of Sm‐doped sample (Figure 5) is oxygen vacancy annihilation. Also, the activation energy for oxygen ion conductivity in perovskites has been observed to increase with increasing oxygen occupancy within the range from 0.5 to 2.0 eV 37,38 . Hence both the decrease in σ 0 and small increase in E a suggest a decrease in oxygen vacancy concentration with the addition of Sm.…”
Section: Discussionmentioning
confidence: 91%